How do Chinese as a second language (CSL) learners acquire orthographic knowledge: component, structure and position regularity. Issue 3 (5th October 2021) - Loh, Elizabeth Ka Yee; Liao, Xian; Leung, Shing On; Tam, Loretta Chung Wing
Abstract: Learning Chinese characters could be challenging for many CSL learners due to the distinction in orthographic features between the Chinese written system and their first languages. While acquisition of orthographic knowledge could be important for learning Chinese characters, how they can gain knowledge about different aspects of Chinese orthography (i.e. component, structure and position regularity) remains less studied. The component is a basic perceptual constituent of Chinese characters, the character structure is the configuration layout formed by relative positions of components. Many components are supposed to follow the implicit position regularity rule when they are integrated to form characters. In this study, a total of 213 CSL students in Hong Kong were invited to complete three tasks measuring students' component knowledge, structural knowledge, and position regularity knowledge. It has been found that overall CSL students' performance in these tasks seemed to be affected by character structures. Furthermore, we found that component knowledge had an indirect effect on position regularity knowledge via the mediation of structural knowledge, which showed a possible link about how learners gradually understand complex orthographic rules based on the perceptual observation. Implications for the teaching and learning of the Chinese language were also discussed.